Gum-gut axis: The potential role of salivary biomarkers in the diagnosis and monitoring progress of inflammatory bowel diseases - Hanan Balto; Solaiman Al-Hadlaq; Abdulmalik Alhadlaq; Afaf El-Ansary (Elsevier, 2023)
The gut mucosa is an extension of the oral mucosa, and both are directly linked. There is emerging evidence that pathogenic oral microbiome contributes greatly to the risk of developing Inflammatory Bowel Disease (IBD). Dysbiosis of the oral microbiota can interfere with the host immune system's ability to respond normally, thereby increasing the development of periodontitis which raises the risk of IBD, cancer, rheumatoid arthritis, cardiovascular disease, and other complex disease processes. Salivary biomarkers are possibly important for determining the incidence, severity, and remission of IBD. Nevertheless, clinical translation of biomarker knowledge from lab to clinical practice needs further studies that identify biomarkers related to the transitional phase between healthy and unhealthy. In this review, the bidirectional pathway between the gut and the oral cavity was investigated and several aspects were discussed.